A Study of Shading Device Configuration on the Natural Ventilation Efficiency and Energy Performance of a Double Skin Façade. (2015) - Lee, Jeehwan; Alshayeb, Mohammed; Chang, Jae D.
Abstract: Studies have shown that double skin facades (DSFs) are capable of improving building energy performance using the stack effect to dissipate heat as well as shading devices to screen undesired solar heat transmission. In this simulation study, the scenarios were made based on shading device configuration to see relationships among airflow patterns, the air velocity, the air temperature and the annual energy consumption. The ultimate goals of this study are not only to investigate the optimal controls of shading devices in naturally ventilated buildings but also to maintain the balance of natural ventilation efficiency and building energy saving. Initial findings indicated that that the air temperature and airflow patterns were highly dependent on the shading device configuration. In cases of 30-, 60- and 90-degree angle of horizontal shading devices, the air temperature of an exterior facing side's air cavity was greater than that of vertical shading devices. It was also found that the mean air velocity and airflow patterns of both shading devices at 0-degree angle were improved than the case of 90-degree angle. With regard to an annual energy consumption, it was discovered that horizontal shading devices at 30-, 60-, and 90-degree angle were more effective to reduce the energy use by 0.4%, 2.6% and 6.4% respectively than the case of 0-degree angle.